Petrology and geochemistry of olivine‐phyric shergottites LAR 12095 and LAR 12240: Implications for their petrogenetic history on Mars. (21st February 2019) - Dunham, Emilie T.; Balta, J. Brian; Wadhwa, Meenakshi; Sharp, Thomas G.; M Sween, Harry Y.
Abstract: Larkman Nunatak (LAR) 12095 and LAR 12240 are recent olivine‐phyric shergottite finds. We report the results of petrographic and chemical analyses of these two samples to understand their petrogenesis on Mars. Based on our analyses, we suggest that these samples are likely paired and are most similar to other depleted olivine‐phyric shergottites, particularly Dar al Gani (DaG) 476 and Sayh al Uhaymir (SaU) 005 (and samples paired with those). The olivine megacryst cores in LAR 12095 and LAR 12240 are not in equilibrium with the groundmass olivines. We infer that these megacrysts are phenocrysts and their major element compositions have been homogenized by diffusion (the cores of the olivine megacrysts have Mg# 70, whereas megacryst rims and groundmass olivines typically have Mg# 58–60). The rare earth element (REE) microdistributions in the various phases (olivine, low‐ and high‐Ca pyroxene, maskelynite, and merrillite) in both samples are similar and support the likelihood that these two shergottites are indeed paired. The calculated parent melt (i.e., in equilibrium with the low‐Ca pyroxene, which is one of the earliest formed REE‐bearing minerals) has an REE pattern parallel to that of melt in equilibrium with merrillite (i.e., one of the last‐formed minerals). This suggests that the LAR 12095/12240 paired shergottites represent the product of closed‐system fractional crystallization following magma emplacement and crystal accumulation. Utilizing the europium oxybarometer, we estimate that the magmatic oxygen fugacity early in the crystallization sequence was IW. Finally, petrographic evidence indicates that LAR 12095/12240 experienced extensive shock prior to being ejected from Mars.